Den levende røst - Hansen, Uffe (Grundtvig-Studier, 1958)
The Living Voice. By Uffe Hansen. Grundtvig worked for many years to deepen and strengthen his ideas of the true nature of Christianity and its revelation. With the experiences of his childhood as a background he had in 1825 recognised, and proclaimed in “Kirkens Gienmæle” (“ The Church’s Answer” ), the new conception that the Church and Christianity have not sprung forth from the Scriptures, but from the living word which Jesus preached here below with a voice that could be heard, and which He empowered His disciples to bring to the peoples of the whole world. This living word comes to the individual in the community of the Church, to us, in baptism and the Lord’s Supper, which are the work of the Risen Savior Himself, in which He Himself speaks to us. In this fashion in the course of time Grundtvig set forth his ideas on countless occasions in speech and writing, and many poems and hymns give more or less clear expression to them. But even in his eightieth year he had not finished all he had to say about them, and the Danish Church had not understood what he said. An article by Bishop Martensen in I863 on “The Inspiration of the Apostles” , caused Grundtvig to take the question up for fresh treatment, partly at the first “meeting of his friends” , which was held in Copenhagen during the days immediately after his eightieth birthday, and partly in a series of poems, the longest of which was printed and distributed to all who took part in the meeting. His poem, “Den levende Røst” (“ The Living Voice” ), is 52 pages long and contains 248 verses in a verse-form of the old Scandinavian type, which Grundtvig had already used in 1808. Manuscripts recently found contain a number of drafts of the poem, which indicate the extent of the preliminary work that was done for it and that has not yet been dealt with by those engaged in research of Grundtvig’s writings. The article throws light on the main ideas of the poem and many obscure passages by means of a survey which can only be understood by readers well versed in Danish. In the second edition of the poem, which came out in December, 1863, there is a supplementary, and shorter, poetic exposition of the same ideas verses with the title: “Himlens Røst” (“The Voice of Heaven” ). And finally Grundtvig summarised the essential points in these poems in a hymn nine verses long: “Hører du Røsten?” (“Dost thou hear the Voice?” ), which appeared in the eighth edition of “Fest-Psalmer” (“ Festival Hymns” ) in 1864. The poet did not consider it sufficient to clarify his ideas about this important matter for himself and to try to give his friends an understanding of them, but his aim must also have been to get the Church to utter them in song as its confession of faith with thanks to God.